IFLA journal. - International Federation of Library Associations; International Federation of Library Associations and Institutions (London Thousand Oaks Sage Publications, 1975)
Covers news of current IFLA activities and articles, selected to reflect the variety of the international information profession, ranging from freedom of information, preservation, services to the visually impaired and intellectual property.
English with summaries in French and German.
Official journal of: International Federation of Library Associations, 1975-1976; International Federation of Library Associations and Institutions, 1977-
Description based on: Vol. 1, no. 1 (Jan. 1975); title from journal information screen (Sage, viewed Sept. 24, 2008).
Keywords: International Federation of Library Associations and Institutions -- Periodicals; International Federation of Library Associations -- Periodicals; International librarianship -- Periodicals; Library cooperation -- Periodicals; Library science -- Periodicals; Library science—Societies, etc. -- Periodicals; Library science